Anti-ulcer activity of arachidonic acid (PUFA) oils in different induced ulcer animal models - Arumugasamy, K.; Kannan, S.; Vora, P. A.; Tyagi, Manoj G. (International Journal of Research in Medical Sciences, 2017)
Background: Ulcers of the lower part of the oesophagus, the stomach and the first part of the duodenum are also known as peptic ulcers. Peptic ulcers can affect people of any age, but they are more common as you get older. There is a focus on research for better tolerated and efficacious anti-ulcer agents. Methods: Effect of anti-ulcer activity of fish oil and Arasco oil was evaluated in different animal models of ulcers i.e. ethanol induced, water immersion and pyloric ligation techniques. The Superoxide dismutase activity in gastric tissue was also ascertained in two groups of animals. The animals received either fish oil (40 µl, PO), Arasco oil (40 µl, PO), omeprazole (20 mg/kg PO) or ranitidine (30 mg/kg PO). The gastro-protection was calculated based on ulcer index, pH and gastric juice volume. Results: The results of this study suggest that poly unsaturated fatty acid (PUFA) contained in fish oil and Arasco oil have moderate anti-ulcer activity although probably lesser in potency than the available anti-ulcer drugs like omeprazole and ranitidine. Conclusion: These results have shown that PUFA containing oils provided moderate gastrointestinal protection in all the induced ulcer models employed. Thus it can be concluded that PUFA containing oils like the Fish oil and Arasco oil have anti-ulcer properties and the mechanisms involved in these actions need to be investigated.